Attenuation or absence of circadian and seasonal rhythms of acute myocardial infarction. Issue 4 (April 1997) - Sayer, J. W.; Wilkinson, P.; Ranjadayalan, K.; Ray, S.; Marchant, B.; Timmis, A. D.
Abstract : OBJECTIVES: To examine the circadian, seasonal, and weekly rhythms of acute myocardial infarction, and to identify subgroups in whom the rhythms are attenuated or absent to provide further information about the mechanisms of the rhythms and the processes responsible for triggering plaque events. DESIGN AND SETTING: Prospective, observational study in a general hospital. PATIENTS AND METHODS: 1225 consecutive patients admitted to a coronary care unit with acute myocardial infarction were studied. Admission rates were calculated according to the hour of the day (circadian rhythm), day of the week (weekly rhythm), and month of year (seasonal rhythm). The data were analysed for variations within the whole group and within subgroups. RESULTS: A weekly rhythm of acute myocardial infarction could not be demonstrated but there was a trend towards higher admission rates at the beginning of the week. However, the time of onset of symptoms showed significant circadian variation for the group as a whole, peaking in the morning (P = 0.006), against an otherwise fairly constant background rate. Subgroup analysis showed complete absence of the circadian rhythm in patients who were diabetic, South Asian, or taking beta blockers or aspirin on admission. Significant seasonal variation in admission rates was also demonstrated for the group as a whole with a winter peak and a summer trough (P = 0.009). Again, no seasonal rhythm could be demonstrated in patients who were diabetic, South Asian, or taking beta blockers or aspirin on admission. CONCLUSIONS: The absence of circadian and seasonal rhythms of acute myocardial infarction in almost identical subgroups suggests that common mechanisms are involved in driving these rhythms. The autonomic nervous system is a likely candidate because the rhythms were absent in patients taking beta blockers as well as in patients in whom derangement of autonomic function commonly occurs.